Necessities detected in patients derived to sanitary center in an ambulance of the urgent transport network after being treated by the 061 emergency team - Sixto Cámara Anguita; Antonio J. Valenzuela Rodríguez (Fundación para el Desarrollo de la Enfermería, 2007)
The integral systems of urgencies and sanitary emergencies has, as resources for the urgent transport of patients, with nonwelfare ambulances, ambulances of basic life support and ambulances of advanced life support. In the two first, due to the ambiguity of the norm, the presence of a nurse to give care is not compulsory. Nevertheless, in the present study, it is detected that, the patients of this study, transferred in nonwelfare ambulance of the urgent transport network to a useful hospitable center with urgency character, once they have been attended by the 061 emergency team, presented/displayed a group of altered basic human necessities, medical levels of dependency as far as autonomy, nurse diagnoses, medical diagnoses, and necessities of pursuit of the restored evolution of the therapeutic technique and that cause the necessity of benefit of nursing care during this transfer.